On the middle class - Michael MacLennan; Beatrix Judice Magalh\~aes (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
The Middle class as a concept has evolved over time, taking on various meanings at various points throughout history, becoming an object to aspire to for poor people, an object of desire for a strong government, a buzzword for politicians the world over, and the source of new customers for firms, and the global economy more broadly. This special issue of Poverty in Focus, exclusively devoted to the exploration of themes related to the middle class is part of a larger endeavour initiated by The International Policy Centre for Inclusive Growth (IPC-IG), in collaboration with the Secretariat for Strategic Affairs of the Office of the Brazilian Presidency, to explore the middle class within a development context at national, regional and international levels. Contributions to this middle-class-themed issue have come from leading scholars and development practitioners from across the globe who have addressed the phenomenon of the middle class from several different ideological, academic and regional perspectives to explore a variety of issues in relation to the significance of a growing middle class and overall development achievements. [...]
Keywords: 330